If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + -6 + -9 = 3 Reorder the terms: -6 + -9 + 4g = 3 Combine like terms: -6 + -9 = -15 -15 + 4g = 3 Solving -15 + 4g = 3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 4g = 3 + 15 Combine like terms: -15 + 15 = 0 0 + 4g = 3 + 15 4g = 3 + 15 Combine like terms: 3 + 15 = 18 4g = 18 Divide each side by '4'. g = 4.5 Simplifying g = 4.5
| 3=5-2a | | 8x-1=8(x-3) | | 5x+8(-4x-9)=-10(-2x-9)+26 | | x^2-6x-96=0 | | 2k-1=-5+3k | | 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 | | 7x+5x-38=95-7x | | 2k-1=-5+2k | | 5b-13=3b+1 | | t=6s+18.01 | | 5z+30=40 | | 5-3p+9=13p+8 | | 3f+2=5 | | 5-4p=11 | | (5x-1)(x-5)=0 | | 0=324+2*3.65*x | | 9-(x+6)=9x-7 | | 0.3x-2.9=4.7x+2.6 | | 9x^4-25x^3+16x^2=0 | | 4n+5n=27 | | -2x^2+17x-35=0 | | (10x-10)=(8x+14) | | -8+3r=-3+2r | | 6+x+6+x=6x | | -8x+11+9x=2+x+9 | | 10r=4r+12 | | 15-(3m-5)=32 | | t+10=7r-14 | | X-4=4-3x |